Whole Exon Deletion in the GFAP Gene Is a Novel Molecular Mechanism Causing Alexander Disease - Green, Lydia; Berry, Ian R.; Childs, Anne-Marie; McCullagh, Helen; Jose, Sandhya; Warren, Dan; Craven, Ian; Camm, Nick; Prescott, Katrina; van der Knaap, Marjo S.; Sheridan, Eamonn; Livingston, John H. (Neuropediatrics, 2018)
Alexander disease (AD) is a leukodystrophy caused by heterozygous mutations in the gene encoding the glial fibrillary acidic protein (GFAP). Currently, de novo heterozygous missense mutations in the GFAP gene are identified in over 95% of patients with AD. However, patients with biopsy-proven AD have been reported in whom no GFAP mutation has been identified. We report identical twin boys presenting in infancy with seizures and developmental delay in whom MR appearances were suggestive of AD with the exception of an unusual, bilateral, arc of calcification at the frontal white–gray junction. Initial mutation screening of the GFAP gene did not identify a mutation. Whole exome sequencing in both brothers revealed a de novo heterozygous in-frame deletion of the whole of exon 5 of the GFAP gene. Mutations in the GFAP gene are thought to result in a toxic effect of mutant GFAP disrupting the formation of the normal intermediate filament network and resulting in Rosenthal fiber formation, which has hitherto not been linked to exonic scale copy number variants in GFAP. Further studies on mutation negative AD patients are warranted to determine whether a similar mechanism underlies their disease.
Keywords: Alexander disease; leukodystrophy; GFAP gene; whole exon deletion; intracranial calcification